Implementasi Algoritma Raita Pada Aplikasi Hukum Kanonik Berbasis Mobile - Efidoren L Nainggolan; Muhammad Syahrizal; Saidi Ramadan Siregar (JURIKOM (Jurnal Riset Komputer), 2020)
Canonical law is an internal church law governing the Catholic Church, Eastern Orthodox Church, Eastern Orthodox Church, Anglican Communion. How the laws of the church are governed, interpreted and sometimes examined differ fundamentally between the three church bodies. in all three traditions, a canon was originally a rule accepted by an assembly, these canons formed the basis for canon law. Raita algorithm is part of the exact string matching algorithm, which is matching the string exactly with the arrangement of characters in the matched string that has the same number or sequence of characters in the string. Matching strings on the raita algorithm is done through a shift from the right of the character then to the left of the character and to the middle of the character. The problem in this research is the content of canon law in general consists of a very large number of pages of books, this makes it difficult for canonical law users to find the contents needed, then in the search it takes time to find the contents of canonical law that are searched for too many search problems. that is, too much time must be needed to find the contents of the canonical law sought